Your first leadership job : how catalyst leaders bring out the best in others - Byham, Tacy (John Wiley & Sons, 2015)
Becoming the Very Best First-Time Leader Congratulations! You're now in charge. Perhaps it's your first time as a leader, or maybe you want to fine-tune your skills. Either way, you've begun one of the most rewarding chapters of your career. But, like many beginnings, the first few years can be challenging. Fortunately, you don't have to tackle this challenge on your own. Your First Leadership Job gives you practical advice straight from others who have walked in your shoes. Not only does it include dozens of tools to ensure your success, but it's also based on the authors' and DDI's extens.